Evaluation of Stability of Earth-Fill Dam Based on Strength of Frozen Zones of its Profile (Otsenka Ustoychivosti Zemlyanoy Plotiny po Prochnosti Promerzlykh zon Yeye Profilya) - Kuznetsov,G I (1977)
When planning a permafrost dam it is necessary to consider that the freezing of its lower wedge due to natural cooling of the surface of the lower slopes and the transfer of cold from the permafrost curtain may take 3 to 4 years if the soil is not allowed to freeze layer by layer during the filling process. This report discusses the strength and stability of earth filled dams based on durability of frozen zones of its profile. (Author) Trans. of unidentified Russian report p182-187.